Legal Certainty and Substantive Justice in Inherited Land Disputes: Legal Certainty and Substantive Justice in Inherited Land Disputes - Prakoso, Danies Teguh; Idrus, Muammar Alay; Masyhur (Al-Risalah, 2025)
This study analyzes the legal status of inherited land ownership after title transfer and the legitimacy of tax payment claims by other heirs. Despite the formal transfer and registration of inherited land providing legal certainty through certificates, disputes often arise when other heirs demand tax payments, highlighting a tension between administrative law and perceived fairness. This research fills a gap in understanding how Indonesian land law, civil inheritance law, and tax regulations intersect in post-transfer inheritance disputes. Using a normative juridical method with a qualitative approach, the study applies statutory, case, and conceptual analyses. Primary sources include UU No. 5 of 1960, KUHPerdata, PP No. 24 of 1997, and tax provisions on PBB and BPHTB, while secondary sources comprise literature and court decisions. Analysis interprets legal norms and connects them to social practices, emphasizing how legal certainty, substantive justice, and social utility can be balanced. The findings demonstrate that inherited land ownership post-transfer is legally valid and protected by certificates, whereas tax claims by other heirs are justified only for undivided obligations proportionate to each heir’s share, consistent with KUHPerdata principles. Applying Gustav Radbruch’s theory of legal certainty and Philipus M. Hadjon’s legal protection framework, the study highlights the need for integrated approaches combining litigation, mediation, and efficient tax administration under PER-8/PJ/2025. The study contributes academically by clarifying the interaction between inheritance law and tax obligations in Indonesia and offers practical guidance for heirs, notaries, BPN, and tax authorities to prevent disputes and ensure equitable distribution